Unobtrusive monitoring of computer interactions to detect cognitive status in elders. - Jimison, H.
The U.S. has experienced a rapid growth in the use of computers by elders. E-mail, Web browsing, and computer games are among the most common routine activities for this group of users. In this paper, we describe techniques for unobtrusively monitoring naturally occurring computer interactions to detect sustained changes in cognitive performance. Researchers have demonstrated the importance of the early detection of cognitive decline. Users over the age of 75 are at risk for medically related cognitive problems and confusion, and early detection allows for more effective clinical intervention. In this paper, we present algorithms for inferring a user's cognitive performance using monitoring data from computer games and psychomotor measurements associated with keyboard entry and mouse movement. The inferences are then used to classify significant performance changes, and additionally, to adapt computer interfaces with tailored hints and assistance when needed. These methods were tested in a group of elders in a residential facility.
Keywords: E-mail.; Cognitive status detection; Computer games; Computer interaction; Data monitoring; Dementia; Elders; Home monitoring; Keyboard entry; Mouse movement; Psychomotor measurement; Unobtrusive monitoring; User cognitive performance